Perceptions and practices of critical success factors in benchmarking implementation in Malaysian automotive manufacturing companies - Baba Md Deros; Sha’ri Mohd Yusof; Azhari Md Salleh (Penerbit ukm, 2006)
This paper presents the results from a survey conducted to measure the Malaysian automotive manufacturing companies’ top management perceptions of importance and practices of critical success factors (CSFs) with respect to benchmarking implementation. The main objective of this paper is to provide empirical evidence on whether there were significant differences in terms of perceptions of importance and actual practices of CSFs in implementing benchmarking. First, between the perception of importance and extent of practice of the overall companies; and secondly between 100% local and joint venture companies. A questionnaire with 49 items was developed by the authors based on previous studies, checked for reliability and validity by experts and practitioners, and applied to create a self-assessment measure of benchmarking practices. Analysis of the survey results showed that there were significant differences between perception of importance and actual practice of CSFs for benchmarking implementation. The paper concludes with some suggestions on how to close the gap between perceptions of importance and practices of CSFs in implementing benchmarking